2016
DOI: 10.5539/jsd.v9n1p256
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Climate Change on Agro-Ecological Based Livelihoods in Africa: A Review

Abstract: Several local studies have been carried out on the impact of climate change on livelihoods and development especially in developing countries. However, there is a general scarcity of literature that makes a comparative appraisal of the impacts of climate change on agro-ecological based livelihoods across the African continent. This paper seeks to address that gap by making a comparative analysis of the effects of climate change on agro-based livelihoods across the African continent, focusing on Eastern, Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 34 publications
0
37
0
1
Order By: Relevance
“…As reported by Makate et al (), higher temperatures that are experienced regularly in Africa have reduced crop yields while encouraging weed and pest proliferation. Studies have shown that climate change and extreme climatic events pose great threats to agricultural production, food security, community health, natural resources, biodiversity, and water availability (Dube, Moyo, & Ncube, ; IPCC, ; Mashizha et al, ), and rural communities are not being spared from the rant. The effects are made worse to the fact that agriculture is the main source of income for most rural households.…”
Section: Climate Change Affects Rural Communitiesmentioning
confidence: 99%
“…As reported by Makate et al (), higher temperatures that are experienced regularly in Africa have reduced crop yields while encouraging weed and pest proliferation. Studies have shown that climate change and extreme climatic events pose great threats to agricultural production, food security, community health, natural resources, biodiversity, and water availability (Dube, Moyo, & Ncube, ; IPCC, ; Mashizha et al, ), and rural communities are not being spared from the rant. The effects are made worse to the fact that agriculture is the main source of income for most rural households.…”
Section: Climate Change Affects Rural Communitiesmentioning
confidence: 99%
“…Sustainable livelihoods frameworks usually distinguish resource‐based from non‐resource‐based livelihoods to spotlight the exposure and sensitivity to natural hazards experienced by the former (DFID, 1999; Birkmann, 2005; Eakin et al, 2012; Antwi‐Agyei et al, 2013; Dube et al, 2016). Agricultural production is commonly weather‐dependent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A wide range of scholars defines global warming as an average increase in the temperature of the atmosphere near the earth's surface and the troposphere. While it can occur from a variety of causes, global warming often refers to the warming due to the increase in emissions of greenhouse gases (GHG) from human activities [1]. GHG include carbon dioxide, water vapour, methane, nitrous oxide, chlorofluorocarbons and others.…”
Section: Introductionmentioning
confidence: 99%